Method for separating waste cotton-polyester blended fabric through subcritical water catalytic acidolysis
Through subcritical water catalytic acid-solving method and recycling technology, the problems of low separation efficiency and high recycling cost in the treatment of waste polyester-cotton blended textiles are solved, efficient separation and resource recycling are achieved, and environmental burden is reduced.
Patent Information
- Application Number
- CN202510042749.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the prior art, when processing waste polyester and cotton blended fabrics, it is difficult to achieve efficient and accurate separation, and the recycling cost is high and the environmental burden is heavy.
The subcritical water catalytic acid-lysis method is used to separate polyester fibers and cellulose powders through the synergistic action of organic acids and Lewis acid catalysts, and carbon microspheres are prepared by recycling the sugar-containing acid solution.
It realizes efficient and precise separation of waste polyester and cotton blended fabrics, reduces production costs, reduces waste emissions, reduces negative impacts on the environment, and obtains high-quality reusable fibers and carbon microspheres.
Smart Images

Figure BDA0005237436630000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile waste treatment and resource recycling, and in particular relates to a method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis. Background Art
[0002] As an important part of the global economic system, the textile industry not only meets people's clothing needs and promotes the development of the fashion industry, but also produces a large amount of waste textiles. As a major category of waste polyester-cotton blended fabrics, their treatment and recycling face many challenges.
[0003] Traditionally, waste polyester-cotton blended fabrics have been handled in a rough manner. Landfill is a common method, but this method not only occupies a large amount of valuable land resources, but also over time, the chemicals in waste textiles may seep out and pollute the soil and groundwater environment, causing long-term and irreversible damage to the ecological balance. Incineration also has serious problems. A large amount of harmful gases will be released during the incineration process, such as persistent organic pollutants such as dioxins and furans, and greenhouse gases such as carbon dioxide, which will undoubtedly aggravate air pollution and have a negative impact on global climate change.
[0004] Although some existing methods attempt to recycle waste polyester-cotton blended fabrics, they still have obvious shortcomings. Physical separation methods, such as mechanical crushing and screening, are difficult to achieve accurate separation of polyester and cotton, and the resulting products are often of low purity and cannot meet the requirements of high-quality reuse. Although some chemical recovery methods can decompose or separate polyester and cotton to a certain extent, the chemical reagents used are highly corrosive or toxic, which not only places extremely high demands on equipment and requires special equipment that is corrosion-resistant and high-temperature resistant, thereby increasing equipment investment costs, but also easily generates a large amount of difficult-to-handle hazardous waste during the treatment process, further increasing the environmental burden. At the same time, the key substances used in these methods, such as catalysts and solvents, are difficult to recycle and reuse, resulting in high overall recovery costs and poor economic benefits, limiting their large-scale industrial application.
[0005] Therefore, how to achieve efficient recovery and recycling of resources and reduce the negative impact on the environment on the basis of effective separation of waste polyester-cotton blended fabrics has become a key issue that needs to be urgently addressed in the current field of textile waste treatment. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis, comprising the following steps:
[0009] (1) pretreating waste polyester-cotton blended fabric to obtain pretreated waste polyester-cotton fabric fragments;
[0010] (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) and the composite catalyst aqueous solution in a reactor, sealing the reactor and performing subcritical water catalytic acid hydrolysis, and obtaining polyester fibers, cellulose powder and a first sugar-containing acid hydrolysis solution after centrifugation and filtration, respectively; the composite catalyst aqueous solution is a mixed aqueous solution of an organic acid and a Lewis acid catalyst;
[0011] (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) to obtain a second sugar-containing acid hydrolysis solution;
[0012] (4) Dehydrating and carbonizing the second sugar-containing acid hydrolyzate obtained in step (3) to obtain carbon microspheres; the dehydration and carbonization temperature is 150 to 180° C.
[0013] Technical principle: By utilizing the special physical and chemical properties of subcritical water and the synergistic effect of organic acid and Lewis acid catalysts, the solubilization and diffusion promotion of reactants by subcritical water at a certain temperature and pressure, combined with the acidic environment provided by organic acid in the composite catalyst aqueous solution to promote the chemical bond breakage of cotton fibers and the principle that Lewis acid catalysts reduce the activation energy of the reaction, the efficient and accurate separation of polyester and cotton in waste polyester-cotton blended fabrics is achieved, polyester fibers are separated, and cotton fibers are decomposed into cellulose powder and glucose. The cellulose powder is recycled and reused, and the glucose and composite catalyst aqueous solution form a sugar-containing Acid hydrolysis solution, the obtained sugar-containing acid hydrolysis solution can be reused for subcritical water catalytic acid hydrolysis of waste polyester-cotton blended fabrics; and the recycled sugar-containing acid hydrolysis solution can be dehydrated and carbonized to obtain carbon microspheres, and in the process of dehydration and carbonization, since the sugar-containing acid hydrolysis solution contains organic acid, it can ionize hydrogen ions in the solution, prompting the hydroxyl groups of glucose molecules to be protonated, thereby accelerating dehydration; at the same time, it can be used as a catalyst to form an intermediate complex with the reactants, change the reaction pathway, reduce the activation energy, promote hydrolysis and polycondensation reactions, make glucose more quickly converted into active intermediates and accelerate the formation of carbonaceous structures, thereby reducing the temperature of dehydration and carbonization. At the same time, in the initial stage of carbonization, organic acids control the uniform and orderly nucleation of carbon microspheres by combining with glucose dehydration products; during the growth process, by adjusting the growth rate, the carbon microspheres grow stably and moderately, avoiding irregular morphology and uneven particle size; and can be adsorbed on the surface of carbon microspheres to stabilize the structure, prevent agglomeration, and reduce surface defects; in addition, the viscosity and surface tension of the reaction system can be adjusted to optimize mass transfer, and finally obtain carbon microspheres with excellent morphology and structure.
[0014] The present invention adopts a mixed aqueous solution of an organic acid and a Lewis acid catalyst to catalyze the acidolysis of waste polyester-cotton blended fabrics. The organic acid can make chemical bonds such as glycosidic bonds of cotton fibers easier to break in a subcritical water environment, and the Lewis acid catalyst further reduces the energy barrier of the reaction. The two synergistically significantly improve the degradation rate and selectivity of the cotton fibers, thereby efficiently separating the cotton fibers from the polyester fibers, while maintaining good mechanical properties and other qualities of the separated polyester fibers, and can be directly reused in the textile industry.
[0015] Preferably, in step (1), the pretreatment comprises the following steps: cutting the waste polyester-cotton blended fabric into pieces, and then soaking them in sodium carbonate solution and hydrogen peroxide solution in sequence.
[0016] Preferably, the mass concentration of the sodium carbonate solution is 0.3-1.2%; the soaking temperature of the sodium carbonate solution is 45-55° C., and the soaking time is 25-50 min.
[0017] Preferably, the mass concentration of the hydrogen peroxide solution is 1.5-2.5%; the soaking temperature of the hydrogen peroxide solution is 55-65° C., and the soaking time is 15-35 min.
[0018] Preferably, in step (2), the mass concentration of the organic acid in the composite catalyst aqueous solution is 4-10%, and the mass concentration of the Lewis acid catalyst is 0.15-0.8%.
[0019] Preferably, in step (2), the solid-to-liquid ratio of the pretreated waste polyester-cotton fabric fragments to the composite catalyst aqueous solution is 1:(35-90).
[0020] Preferably, in step (2), the organic acid is selected from one or more of oxalic acid, acetic acid, tartaric acid and malic acid.
[0021] Preferably, in step (2), the Lewis acid catalyst is selected from one or more of copper sulfate, zinc sulfate and manganese acetate.
[0022] Preferably, in step (2), the subcritical water catalytic acidolysis adopts staged heating; the staged heating is specifically: firstly heating to 125-135°C at a heating rate of 1.2-2.8°C / min, keeping warm for 8-18min, then heating to 155-170°C at a heating rate of 3.5-5.5°C / min, keeping warm for 0.5-2.0h.
[0023] Preferably, in step (3), steps (1) to (2) are repeated 0 to 6 times.
[0024] Preferably, in step (4), the temperature of the dehydration carbonization is 150-160° C., and the time is 1.0-3.0 h.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis provided by the present invention can efficiently separate cotton fibers from polyester fibers, and the polyester fibers obtained after separation can still maintain good mechanical properties and can be directly reused in the textile industry; the structural properties of the cellulose powder obtained after separation are basically consistent with those of commercial microcrystalline cellulose MCC, and can be directly used in the coating, food and other industries; by reusing the sugar-containing acidolysis liquid to perform subcritical water catalytic acidolysis on the waste polyester-cotton blended fabric, and preparing carbon microspheres through dehydration and carbonization after the recycling is completed, the degradation products of the cotton fibers and the catalyst used in the acidolysis reaction process are fully utilized, and the efficient recovery and recycling of resources are realized, the production cost is greatly reduced, the waste discharge is reduced, and the negative impact on the environment is reduced.
[0027] The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis provided by the present invention causes less damage to polyester fibers, can maintain the mechanical properties of the original polyester fibers to the greatest extent, and the separated polyester fibers can be directly reused in the textile industry.
[0028] The method provided by the present invention can also reduce the temperature of dehydration carbonization, reduce energy consumption, and obtain carbon microspheres with a higher specific surface area, which can be used in the field of water treatment. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0031] The embodiment of the present invention provides a method for separating waste polyester-cotton blended fabric by subcritical water catalytic acidolysis, comprising the following steps:
[0032] (1) pretreating waste polyester-cotton blended fabric to obtain pretreated waste polyester-cotton fabric fragments;
[0033] (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) and the composite catalyst aqueous solution in a reactor, sealing the reactor and performing subcritical water catalytic acid hydrolysis, and obtaining polyester fibers, cellulose powder and a first sugar-containing acid hydrolysis solution after centrifugation and filtration, respectively; the composite catalyst aqueous solution is a mixed aqueous solution of an organic acid and a Lewis acid catalyst;
[0034] (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) to obtain a second sugar-containing acid hydrolysis solution;
[0035] (4) Dehydrating and carbonizing the second sugar-containing acid hydrolyzate obtained in step (3) to obtain carbon microspheres; the dehydration and carbonization temperature is 150 to 180° C.
[0036] In a preferred embodiment, in step (1), the polyester-cotton blending ratio of the waste polyester-cotton blended fabric is (60:40) to (70:30).
[0037] In a preferred embodiment, in step (1), the pretreatment comprises the following steps: cutting the waste polyester-cotton blended fabric into pieces, and then soaking them in sodium carbonate solution and hydrogen peroxide solution in sequence. The present invention soaks the waste polyester-cotton blended fabric in sodium carbonate solution and hydrogen peroxide solution to remove grease, residual dyes and impurities on the surface of the fabric, thereby providing a good basis for the subsequent subcritical water catalytic acidolysis reaction and improving the overall recycling effect.
[0038] In a preferred embodiment, the shredding is: cutting the waste polyester-cotton blended fabric into pieces with a side length of 3 to 7 cm.
[0039] In a preferred embodiment, the mass concentration of the sodium carbonate solution is 0.3-1.2%; the soaking temperature of the sodium carbonate solution is 45-55°C; the soaking time of the sodium carbonate solution is 25-50 minutes; and the solid-liquid ratio of the sodium carbonate solution is 1:(5-20). The present invention controls the concentration, soaking temperature and soaking time of the sodium carbonate solution within the above ranges, thereby achieving the purpose of improving the surface quality of the fabric and avoiding damage to the polyester fiber.
[0040] In a preferred embodiment, after soaking with the sodium carbonate solution, the step further includes rinsing with clean water for 4 to 6 times until the pH value of the rinse water is close to neutral.
[0041] In a preferred embodiment, the mass concentration of the hydrogen peroxide solution is 1.5-2.5%; the temperature for soaking in the hydrogen peroxide solution is 55-65°C; the time for soaking in the hydrogen peroxide solution is 15-35 minutes; and the solid-liquid ratio for soaking in the hydrogen peroxide solution is 1:(4-30). The present invention controls the concentration, soaking temperature and soaking time of the hydrogen peroxide solution within the above ranges, which can effectively remove grease, impurities and residual dyes on the surface of the fabric, improve the surface quality of the fabric, and thus enhance the overall recycling effect.
[0042] In a preferred embodiment, the step of rinsing with clean water 4 to 6 times is further included after soaking with the hydrogen peroxide solution.
[0043] In a preferred embodiment, in step (2), the mass concentration of the organic acid in the composite catalyst aqueous solution is 4-10%; the mass concentration of the Lewis acid catalyst is 0.15-0.8%. In the present invention, if the concentration of the organic acid is too low, it is difficult to create a sufficient acidic environment and provide sufficient active sites, resulting in poor separation effect of waste polyester-cotton blended fabrics, reduced recovery rates of polyester and cellulose powders, reduced strength of polyester due to impurities, and poor performance of carbon microspheres due to impurities. If the concentration is too high, it will cause overreaction, damage polyester fibers and cotton fibers, reduce polyester recovery rate and strength, and cause problems such as uneven particle size and increased surface defects of carbon microspheres due to residues during carbon microsphere preparation. If the concentration of the Lewis acid catalyst is too low, the effect of synergistic catalysis in separating waste polyester-cotton blended fabrics is not obvious, the separation efficiency is low, the time is long and the degree is not ideal. If the concentration is too high, it is easy to cause side reactions, damage polyester fibers, reduce separation effect, cellulose powder recovery rate, polyester recovery rate and strength, and interfere with the preparation process of carbon microspheres, resulting in unstable performance.
[0044] In a preferred embodiment, in step (2), the solid-to-liquid ratio of the pretreated waste polyester-cotton fabric fragments and the composite catalyst aqueous solution is 1:(35-90). If the solid-to-liquid ratio of the pretreated waste polyester-cotton fabric fragments and the composite catalyst aqueous solution in the present invention is too small, the catalyst cannot fully contact the fabric to exert its effect, resulting in incomplete separation of polyester and cotton, and cotton fibers are likely to remain on the polyester, affecting subsequent treatment. If the reaction system is too large, it will be overly diluted, the effective concentration of the catalyst will be reduced, the reaction rate will be slow, the separation effect will be poor, the time consumption will be extended, and it will be difficult to achieve the ideal separation degree.
[0045] In a preferred embodiment, in step (2), the organic acid is selected from one or more of oxalic acid, acetic acid, tartaric acid, and malic acid. The organic acid in the present invention can make chemical bonds such as glycosidic bonds of cotton fibers more easily break in a subcritical water environment, and synergizes with Lewis acid catalysts to significantly improve the degradation rate and selectivity of cotton fibers, thereby efficiently separating cotton fibers from polyester fibers; at the same time, the use of organic acids also reduces the temperature of subsequent dehydration and carbonization, and improves the particle size and particle size distribution, specific surface area, pore structure, and surface chemical stability of carbon microspheres.
[0046] In a preferred embodiment, in step (2), the Lewis acid catalyst is selected from one or more of copper sulfate, zinc sulfate, and manganese acetate. The Lewis acid catalyst in the present invention can reduce the energy barrier of the subcritical water catalytic acidolysis reaction, and synergize with the organic acid to significantly improve the degradation rate and selectivity of the cotton fiber, thereby efficiently separating the cotton fiber from the polyester fiber, while maintaining the quality of the separated polyester fiber such as good mechanical properties.
[0047] In a preferred embodiment, in step (2), the subcritical water catalytic acidolysis adopts staged heating; the staged heating is specifically: firstly heating to 125-135°C at a heating rate of 1.2-2.8°C / min, keeping warm for 8-18min, then heating to 155-170°C at a heating rate of 3.5-5.5°C / min, keeping warm for 0.5-2.0h. The staged heating strategy is adopted in the subcritical water catalytic acidolysis process of the present invention, which not only ensures the full progress of the reaction, but also avoids the damage to the fiber caused by excessive reaction.
[0048] In a preferred embodiment, in step (2), the pressure of the subcritical water catalytic acidolysis is 0.5 to 5 MPa.
[0049] In a preferred embodiment, in step (2), the centrifugal speed is 5000-12000 rpm, and the time is 20-30 min.
[0050] In a preferred embodiment, in step (2), the mesh size of the sieve used for filtration is 80 to 180 meshes.
[0051] In a preferred embodiment, in step (2), the solid product obtained by centrifugation is washed with water for multiple times before filtering, and then dried in an oven at 60-80° C. for 3-9 hours.
[0052] In a preferred embodiment, in step (3), the number of repetitions of steps (1) to (2) is 0 to 6 times, that is, the number of recycling of the sugar-containing acid hydrolysis solution is 0 to 6 times. The present invention not only significantly improves the utilization efficiency of the acid hydrolysis reaction solution and effectively reduces the production cost by reusing the sugar-containing acid hydrolysis solution, but also the sugar content of the acid hydrolysis solution gradually increases with the increase in the number of cycles, which promotes the increase in the yield of carbon microspheres and brings dual gains in economic benefits and production benefits.
[0053] In a preferred embodiment, in step (4), the temperature of the dehydration carbonization is 150-180°C, more preferably 150-160°C; the time of the dehydration carbonization is 1.0-3.0h, more preferably 1.0-2.0h. During the dehydration carbonization process, the sugars in the sugar-containing acid hydrolyzate are dehydrated and polycondensed after the temperature is raised, and grow uniformly around the center under the action of the catalyst to form a carbonaceous skeleton isotropically. During the dehydration carbonization process, the organic acid can stabilize and improve the structure of the carbon microspheres, and the volatiles are discharged to densify the carbon microspheres, completing the transformation from the sugar-containing acid hydrolyzate to the carbon microspheres. The organic acid in the acid hydrolyzate forms a strong chemical chain with the dehydration carbonization product, and the Lewis acid catalyst interacts with the sugar substance, and the electron pair it accepts interacts with the sugar functional group and changes its own coordination environment or generates new active species, thereby improving the graphitization degree of the carbon microspheres, increasing the specific surface area, and improving the stability, so that the carbon microspheres are improved in terms of conductivity, mechanical properties, adsorption and catalytic activity, chemical and thermal stability, etc.
[0054] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0055] Example 1
[0056] A method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis, the specific steps are as follows:
[0057] (1) 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 65:35 was taken, cut into pieces with a side length of 3 cm, and placed in a sodium carbonate solution with a mass concentration of 0.3% according to a solid-liquid ratio of 1:5, soaked at 45° C. for 50 minutes, and then rinsed with clean water 6 times until the pH value of the rinse water is close to neutral; then the fabric pieces were placed in a hydrogen peroxide solution with a mass concentration of 1.5% according to a solid-liquid ratio of 1:4, soaked at 55° C. for 35 minutes, and then rinsed with clean water 6 times to obtain pretreated waste polyester-cotton fabric pieces.
[0058] (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) into a high-pressure reactor, adding a composite catalyst aqueous solution composed of acetic acid and copper sulfate, wherein the mass concentration of acetic acid is 4%, the mass concentration of copper sulfate is 0.15%, and the solid-liquid ratio of the pretreated waste polyester-cotton fabric fragments to the composite catalyst aqueous solution is set at 1:35; after sealing the reactor, firstly heating the temperature to 125°C at a heating rate of 1.2°C / min, keeping the temperature for 18 minutes, then heating the temperature to 155°C at a heating rate of 3.5°C / min, the reaction pressure is 0.5MPa, and the reaction is carried out for 0.5h; after the reaction is completed, centrifuging the reaction solution at a speed of 5000rpm for 30min to obtain a solid precipitate and a first sugar-containing acid hydrolyzate; washing the obtained solid precipitate with water for multiple times, drying it in an oven at 62°C for 9h, and then sieving it with an 80-mesh filter to obtain reusable polyester fiber and cellulose powder raw materials, respectively.
[0059] (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) once to obtain a second sugar-containing acid hydrolysis solution;
[0060] (4) Add the second sugar-containing acid hydrolyzate obtained in step (3) into a reactor, set the reactor temperature to 150° C., and perform dehydration and carbonization. After 1 hour, carbon microspheres are obtained.
[0061] Example 2
[0062] A method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis, the specific steps are as follows:
[0063] (1) 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 70:30 was taken, cut into pieces with a side length of 5 cm, and placed in a sodium carbonate solution with a mass concentration of 0.8% according to a solid-liquid ratio of 1:6, soaked at 50° C. for 35 minutes, and then rinsed with clean water 5 times until the pH value of the rinse water is close to neutral; then the fabric pieces were placed in a hydrogen peroxide solution with a mass concentration of 2% according to a solid-liquid ratio of 1:5, soaked at 60° C. for 25 minutes, and then rinsed with clean water 5 times to obtain pretreated waste polyester-cotton fabric pieces.
[0064] (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) into a high-pressure reactor, adding a composite catalyst aqueous solution composed of tartaric acid and zinc sulfate, wherein the mass concentration of tartaric acid is 7%, the mass concentration of zinc sulfate is 0.5%, and the solid-liquid ratio of the pretreated waste polyester-cotton fabric fragments to the composite catalyst aqueous solution is set at 1:60; after sealing the reactor, firstly heating the temperature to 130° C. at a heating rate of 2° C. / min, keeping the temperature for 13 min, then heating the temperature to 160° C. at a heating rate of 4.5° C. / min, the reaction pressure is 0.8 MPa, and the reaction is carried out for 2 h; after the reaction is completed, centrifuging the reaction solution at a speed of 8000 rpm for 20 min to obtain a solid precipitate and a first sugar-containing acid hydrolyzate; washing the obtained solid precipitate with water for multiple times, drying it in an oven at 70° C. for 6 h, and then sieving it with a 130-mesh filter to obtain reusable polyester fiber and cellulose powder raw materials, respectively.
[0065] (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) twice to obtain a second sugar-containing acid hydrolysis solution;
[0066] (4) Add the second sugar-containing acid hydrolyzate obtained in step (3) into a reactor, set the reactor temperature to 160° C., and perform dehydration and carbonization. After 1.5 hours, carbon microspheres are obtained.
[0067] Example 3
[0068] A method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis, the specific steps are as follows:
[0069] (1) 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 60:40 was taken, cut into pieces with a side length of 7 cm, and placed in a sodium carbonate solution with a mass concentration of 1.2% according to a solid-liquid ratio of 1:7, soaked at 55° C. for 25 minutes, and then rinsed with clean water 4 times until the pH value of the rinse water is close to neutral; then the fabric pieces were placed in a hydrogen peroxide solution with a mass concentration of 2.5% according to a solid-liquid ratio of 1:6, soaked at 65° C. for 15 minutes, and then rinsed with clean water 4 times to obtain pretreated waste polyester-cotton fabric pieces.
[0070] (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) into a high-pressure reactor, adding a composite catalyst aqueous solution composed of oxalic acid and manganese acetate, wherein the mass concentration of oxalic acid is 10%, the mass concentration of manganese acetate is 0.8%, and the solid-liquid ratio of the pretreated waste polyester-cotton fabric fragments to the composite catalyst aqueous solution is set at 1:90; after sealing the reactor, firstly heating the temperature to 135°C at a heating rate of 2.8°C / min, maintaining for 8 minutes, then heating the temperature to 170°C at a heating rate of 5.5°C / min, the reaction pressure is 1.2 MPa, and the reaction is carried out for 1.2 hours; after the reaction is completed, the reaction solution is centrifuged at a speed of 6000 rpm for 25 minutes to obtain a solid precipitate and a first sugar-containing acid hydrolyzate; after washing the obtained solid precipitate with water for multiple times, drying it in an oven at 78°C for 3 hours, and then sieving it with a 180-mesh filter to obtain reusable polyester fiber and cellulose powder raw materials, respectively.
[0071] (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) three times to obtain a second sugar-containing acid hydrolysis solution;
[0072] (4) Add the second sugar-containing acid hydrolyzate obtained in step (3) into a reactor, set the reactor temperature to 170° C., and perform dehydration and carbonization. After 2 hours, carbon microspheres are obtained.
[0073] Comparative Example 1
[0074] The difference from Example 1 is that in step (2), only acetic acid is added, that is, an equal volume of acetic acid is used to replace the composite catalyst aqueous solution, and the mass concentration of acetic acid is 4%. The rest is the same as Example 1.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that in step (2), only copper sulfate is added, that is, the composite catalyst aqueous solution is replaced by an equal volume of copper sulfate aqueous solution, and the mass concentration of copper sulfate is 0.15%. Others are the same as in Example 1.
[0077] Comparative Example 3
[0078] The difference from Example 1 is that in step (2), after the reactor is sealed, the temperature is raised to 155° C. at a heating rate of 3.5° C. / min, the reaction pressure is 0.5 MPa, and the reaction is carried out for 0.5 h. The rest is the same as in Example 1.
[0079] Comparative Example 4
[0080] (1) taking 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 65:35, cutting it into pieces with a side length of 3 cm, putting it into a sodium carbonate solution with a mass concentration of 0.3% at a solid-liquid ratio of 1:5, soaking it at 45° C. for 50 min, and then rinsing it with clean water for 6 times until the pH value of the rinse water is close to neutral, thereby obtaining pretreated waste polyester-cotton fabric pieces;
[0081] Steps (2) to (3) are the same as those in Example 1.
[0082] Comparative Example 5
[0083] (1) taking 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 65:35, cutting it into pieces with a side length of 3 cm, placing the fabric pieces in a hydrogen peroxide solution with a mass concentration of 1.5% at a solid-liquid ratio of 1:4, soaking it at 55° C. for 35 min, and then rinsing it with clean water 6 times to obtain pretreated waste polyester-cotton fabric pieces;
[0084] Steps (2) to (3) are the same as those in Example 1.
[0085] Comparative Example 6
[0086] (1) taking 100 g of waste polyester-cotton blended fabric with a polyester-cotton blending ratio of 65:35, cutting it into pieces with a side length of 3 cm, and rinsing it with clean water for 6 times to obtain pretreated waste polyester-cotton fabric pieces;
[0087] Steps (2) to (3) are the same as those in Example 1.
[0088] The breaking strength of the recyclable polyester fibers obtained in step (2) of Examples 1 to 3 and Comparative Examples 1 to 6 was tested by a single fiber stretching method, and the specific surface area of the carbon microspheres obtained in Examples 1 to 3 and Comparative Examples 1 to 6 was tested by a mercury intrusion method. The results are shown in Table 1.
[0089] Table 1 Polyester fiber recovery rate and product properties of Examples 1 to 3 and Comparative Examples 1 to 6
[0090]
[0091] As can be seen from Table 1, the recovery rate of polyester fiber in Examples 1 to 3 of the present invention reached more than 92%, the recovery rate of cellulose powder reached more than 88%, the breaking strength of the recovered polyester fiber reached more than 3.0 N / tex, and the specific surface area of the obtained carbon microspheres reached 150 cm 2 Compared with Example 1, Comparative Example 1 only used acetic acid, the recovery rate of polyester fiber decreased by 23%, the recovery rate of cellulose powder decreased by 20%, the breaking strength of the recovered polyester fiber decreased by 1.0N / tex, and the specific surface area of the obtained carbon microspheres decreased by 81cm 2 / g; In Comparative Example 2, only copper sulfate was used, the recovery rate of polyester fiber decreased by 25%, the recovery rate of cellulose powder decreased by 26%, the breaking strength of the recovered polyester fiber decreased by 1.2N / tex, and the specific surface area of the obtained carbon microspheres decreased by 94cm 2 / g; Comparative Example 3 changed the temperature increase strategy during the subcritical water catalytic acidolysis process, the recovery rate of polyester fiber decreased by 18%, the recovery rate of cellulose powder decreased by 13%, the breaking strength of the recovered polyester fiber decreased by 0.9N / tex, and the specific surface area of the obtained carbon microspheres decreased by 8cm 2 / g; Comparative Examples 4 to 6 changed the pretreatment method of waste polyester-cotton blended fabrics, and the recovery rates of polyester fibers decreased by 13%, 17%, and 28%, respectively, and the recovery rates of cellulose powder decreased by 8%, 20%, and 23%, respectively. The breaking strength of the recovered polyester fibers decreased by 0.6N / tex, 0.8N / tex, and 1.1N / tex, respectively, and the specific surface area of the obtained carbon microspheres decreased by 19cm 2 / g, 21cm 2 / g, 65cm 2 / g.
[0092] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis, characterized in that: The following steps are involved: (1) pretreating waste polyester-cotton blended fabric to obtain pretreated waste polyester-cotton fabric fragments; (2) placing the pretreated waste polyester-cotton fabric fragments obtained in step (1) and the composite catalyst aqueous solution in a reactor, sealing the reactor and performing subcritical water catalytic acid hydrolysis, and obtaining polyester fibers, cellulose powder and a first sugar-containing acid hydrolysis solution after centrifugation and filtration, respectively; the composite catalyst aqueous solution is a mixed aqueous solution of an organic acid and a Lewis acid catalyst; (3) using the first sugar-containing acid hydrolysis solution obtained in step (2) as a catalyst for subcritical water-catalyzed acid hydrolysis, repeating steps (1) to (2) to obtain a second sugar-containing acid hydrolysis solution; (4) Dehydrating and carbonizing the second sugar-containing acid hydrolyzate obtained in step (3) to obtain carbon microspheres; the dehydration and carbonization temperature is 150 to 180° C.
2. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1, characterized in that: In step (1), the pretreatment comprises the following steps: cutting the waste polyester-cotton blended fabric into pieces, and then soaking them in sodium carbonate solution and hydrogen peroxide solution in sequence.
3. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 2, characterized in that: The mass concentration of the sodium carbonate solution is 0.3-1.2%; the soaking temperature of the sodium carbonate solution is 45-55° C., and the soaking time is 25-50 minutes.
4. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 2, characterized in that: The mass concentration of the hydrogen peroxide solution is 1.5-2.5%; the soaking temperature of the hydrogen peroxide solution is 55-65° C., and the soaking time is 15-35 minutes.
5. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1, characterized in that: In step (2), the mass concentration of the organic acid in the composite catalyst aqueous solution is 4-10%, and the mass concentration of the Lewis acid catalyst is 0.15-0.8%.
6. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1, characterized in that: In step (2), the solid-to-liquid ratio of the pretreated waste polyester-cotton fabric fragments and the composite catalyst aqueous solution is 1:(35-90).
7. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1 or 5, characterized in that: In step (2), the organic acid is selected from one or more of oxalic acid, acetic acid, tartaric acid and malic acid.
8. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1 or 5, characterized in that: In step (2), the Lewis acid catalyst is selected from one or two of copper sulfate, zinc sulfate and manganese acetate.
9. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1, characterized in that: In step (2), the subcritical water catalytic acidolysis adopts staged heating; the staged heating is specifically: firstly heating to 125-135°C at a heating rate of 1.2-2.8°C / min, keeping warm for 8-18min, then heating to 155-170°C at a heating rate of 3.5-5.5°C / min, keeping warm for 0.5-2.0h.
10. The method for separating waste polyester-cotton blended fabrics by subcritical water catalytic acidolysis according to claim 1, characterized in that: In step (3), the dehydration carbonization temperature is 150-160° C. and the time is 1.0-3.0 h.
Citation Information
Patent Citations
Method for recycling cotton fibers from waste clothes
CN103665426A
Waste clothing recycling pre-treatment technology
CN104532409A
Method for separating and recovering waste cotton-polyester blended fabric under subcritical water condition
CN106674588A
Recycling method of waste and old cotton-polyester blended fabric under hydro-thermal condition
CN107629245A
Waste cotton-polyester blended fabric separation and utilization method based on acidic hydrogen peroxide solution
CN115594883A